Synergistic osteogenesis promoted by magnetically actuated nano-mechanical stimuli. Issue 48 (4th December 2019) - Hao, Lili; Li, Linlong; Wang, Peng; Wang, Zongliang; Shi, Xincui; Guo, Min; Zhang, Peibiao
Abstract : Synergistic osteogenesis promoted by magnetically actuated mechanical stimuli, induced by the nano-deformation of IO-OA/PLGA nanocomposites under a SMF. Abstract : Functional biomaterials with magnetic properties are considerably useful for regulating cell behavior and promoting bone regeneration. And the combination of such biomaterials with physical environmental cues (such as magnetic fields and mechanical stress) might be more favorable for the regulation of cell function. This study is aimed at investigating the combined effects of magnetically responsive materials and a static magnetic field (SMF) on the osteogenic differentiation of osteoblasts and the potential mechanism involved. In this study, oleic acid modified iron oxide nanoparticles (IO-OA NPs) were utilized to generate homogeneous magnetic nanocomposites with poly(lactide- co -glycolide) (PLGA) used as the base and to enhance the mechanical properties of the composites. In vitro experimental results show that in the presence of an external SMF, cell attachment and osteogenic differentiation were significantly improved using the IO-OA/PLGA composites, as indicated by enhanced alkaline phosphatase (ALP) activity, increased mineralized nodule formation, and upregulated bone-associated gene expression (ALP, OCN, and BMP2), in a dose- and time-dependent manner. Furthermore, the upregulated expression levels of piezo-type mechanosensitive ion channel component 1 (Piezo1), a key receptor for sensing mechanical stimuli, implied that the synergistically enhanced osteogenic differentiation was mainly caused as a result of the mechanical stimuli. Such magnetically actuated mechanical stimuli were induced through the nano-deformation of the magnetic substrate under a SMF, which was directly characterized via in situ scanning using atomic force microscopy (AFM). This study demonstrates that magnetically actuated nano-mechanical stimuli may underpin the synergistic effects of magnetic composites and magnetic stimuli to enhance osteogenic differentiation, and they could form the basis of a potential strategy to accelerate bone formation for bone tissue engineering and regenerative medicine applications.